The 13th Nordic-Baltic Conference of German Scholars 2024, Vilnius University, Abstracts - Bäcker, Iris; Daunorienė, Justina; Plaušinaitytė, Lina; Žeimantienė, Vaiva (Vilnius University Proceedings, 2024)
The abstract book contains the abstracts of the papers presented at the 13th Nordic-Baltic Conference of German Scholars (NBGT2024) from 12 to 14 June 2024 at Vilnius University. The subject-specific focus is on questions of German linguistics, literature and cultural studies as well as the didactics of German as a foreign language. Furthermore, the contributions reflect current political discussions on the status of German in the region. The 63 abstracts are presented in alphabetical order according to the authors’ surnames.